2022
DOI: 10.1038/s41598-022-06268-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intra-abdominal pressure on early kidney transplant outcomes

Abstract: Increased intra-abdominal pressure (IAP) is common among post-surgical patients and may cause organ dysfunction. However, its impact after kidney transplantation on early postoperative complications and graft recovery remains unclear. We designed a prospective, observational cohort study to describe the prevalence and determinants of IAP, as well as its effect on delayed graft function, postoperative complications, and graft recovery. IAP was measured in 205 kidney transplant recipients every 8 h during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…7 Wake Forest University School of Medicine, Atrium Health Wake Forest Baptist Medical Center, Winston-Salem, NC, USA. 8 Outcomes Research Consortium, Cleveland, OH, USA. 9 Perioperative Outcomes and Informatics Collaborative (POIC), Winston-Salem, NC, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Wake Forest University School of Medicine, Atrium Health Wake Forest Baptist Medical Center, Winston-Salem, NC, USA. 8 Outcomes Research Consortium, Cleveland, OH, USA. 9 Perioperative Outcomes and Informatics Collaborative (POIC), Winston-Salem, NC, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…3 and 4) [ 1 ]. Coca et al reported data from 205 kidney transplant patients where intermittently measured high IAP was common and associated with delayed graft function, postoperative complications, and absence of graft function recovery [ 8 ]. In addition, IAP is a prognostic marker when measured during exploratory laparotomy in surgical patients, with higher numbers associated with mortality, a higher SOFA score and prolonged ileus.…”
Section: Intermittent Intra-abdominal Pressure Measurementmentioning
confidence: 99%
“…In 205 patients undergoing kidney transplantation, IAH developed in 78% of patients during the first 3 days after surgery [9]; mean IAPs were 12 mmHg. Higher IAP was associated with higher resistance index and lower urinary output, and the 72 h mean IAP was an independent predictor of delayed graft function, postoperative complications as well as absence of graft recovery.…”
Section: Epidemiology Updatementioning
confidence: 99%